Fenestranes in Synthesis: Unique and Highly Inspiring Scaffolds. Issue 49 (7th November 2013) - Boudhar, Aicha; Charpenay, Mélanie; Blond, Gaëlle; Suffert, Jean
Abstract The scaffold of fenestranes is quite unique, as it contains four condensed cycles and a distorted tetracoordinated central carbon atom with bond angles greater than the regular 109°28". In this Minireview, a detailed overview on the developments regarding this compound class, including their synthesis, is given for the time period since 2006. In the past years, natural products that belong to the class of heterofenestranes have been isolated and their syntheses will also be discussed.